Enzima alfa amilase exógena e biocolina para bovinos - Barbizan, Mariana (2023)
This study sought to evaluate the supply of a-amylase enzyme and biocolin on the nutritional and productive performance of ruminants. To evaluate the use of the a-amylase enzyme, a study was carried out using 45 crossbred heifers (½ Brahman × ½ Nelore), with an average age and average initial body weight (BW) of 22 months and 314.7 ± 4.34 kg. The design used was entirely randomized with a 2 × 2 factorial arrangement to evaluate the addition or not of the a-amylase enzyme (0 or 667 kilo new units (KNU)/kg of concentrate) and two levels of supplementation (3 or 6 g of concentrate/kg of BW). Regardless of the amount of supplement offered, the a-amylase enzyme had no effect (P > 0.05) on consumption, digestibility and animal performance. The addition of a-amylase enzyme to the concentrate supplement does not improve the nutritional and productive performance of beef heifers kept on tropical pasture. Offering 6 g/kg CP of concentrate supplement increases the productive performance of heifers without affecting the consumption of high quality tropical forage. To evaluate the effect of biocoline, five castrated male Jersey cattle with a body weight of 791.60 ± 14.95 kg and a rumen cannula were divided into 5 x 5 Latin squares in a 2 × 2 + 1 factorial design. The treatments used were two doses of biocoline (3 and 6 g of biocoline/100 kg of body weight), two biocoline administration sites (rumen and abomasum) and a control treatment in which no biocoline was administered. The administration of biocoline in different amounts and at different sites had no effect (P > 0.05) on intake, digestibility, rumen and blood parameters. The administration of 6 g of biocoline/100 kg of BW tended to increase the digestibility of ether extract. Doses higher than 6 g of biocoline/100 kg of CP can be evaluated in future studies to better understand the potential of biocoline as an emulsifier in diets with high lipid content and sources of rapid release into the rumen environment of cattle.